Gastrodia pushparaga (Orchidaceae, Epidendroideae, Gastrodieae), a new species from Sri Lanka - Gopallawa, Bhathiya; Perera, Amila; Madola, Indrakheela; Yakandawala, Deepthi; Kumar, Pankaj; Jayawickrama, Harsha; Chase, Mark W. (Phytotaxa, 2023)
N/A